PLATINUM-GROUP MINERALS IN LODE AND PLACER DEPOSITS ASSOCIATED WITH THE URAL-ALASKAN-TYPE GAL'MOENAN COMPLEX, KORYAK-KAMCHATKA PLATINUM BELT, RUSSIA - Tolstykh N.D.; Sidorov E.G.; Kozlov A.P. (My University, 2004)
Mineralization in the platinum-group elements occurs in lodes in the dunite – clinopyroxenite – gabbro Gal’moenan complex, in the Koryak–Kamchatka Platinum Belt of Russia, and in associated placers, namely those along the Levtyrinyvayam River and Ledyanoy and Penistiy creeks at different distances from the source. The grains of Pt–Fe alloy in lode deposits are isoferroplatinum and have Pt3Fe compositions, whereas those in the Levtyrinyvayam River placer range in composition from native to ferroan platinum and having iron contents generally higher than in the lodes (30–35 at.% Fe). Platinum grains from the Ledyanoy Creek placer are larger and more commonly intergrown with chromite than those from the Levtyrinyvayam River. Minor elements, which are indicators of conditions of formation of the Pt–Fe alloy, exhibit different concentrations in lodes and in the nearby placers. Platinum–iron alloy from the Levtyrinyvayam placer, the farthest from the source, represents the eroded upper apical part of the intrusion, and contains mainly Pd. The Penistiy placer receives platinum from dunite and pyroxenite of a marginal facies of the complex, and thus platinum–iron alloy bearing Rh–Ir and Pd–Rh. Placer isoferroplatinum deposited in the Ledyanoy Creek, which drains dunite and chromite-bearing rocks in the south of the intrusion, is rich in Ir (up to 6.98 wt.%), as is the Pt– Fe alloy in the Gal’moenan complex (4.34 wt.% Ir). Most grains contain also a relatively high Rh content. Isoferroplatinum + iridium and isoferroplatinum + osmium are two main primary magmatic parageneses revealed in both placers and lodes, though the first is more commonly found in lodes and in the Ledyanoy Creek placer, and the latter in the Levtyrinyvayam River placer. Lodes mostly contain laurite, RuS2, and the Levtyrinyvayam placer bears all varieties of (Ru,Os)S2, including Ru-free Rh-rich erlichmanite (Os,Rh)S2. The irarsite – hollingworthite series predominates in lodes, and the irarsite – platarsite and osarsite – platarsite series predominate in the Levtyrinyvayam placer. Sperrylite in lodes may contain up to 6.94 wt.% Sb, and thus differs from that in placers. The phase (Pt0.96Fe0.02)0.98(As1.17Sb0.75S0.09)2, a member of the sperrylite – geversite solid solution, has been found in a lode. Complete solid-solution between RuS2 and RuAsS on one hand, and PtAsS and PtAs2 on the other, is demonstrated. In the Gal’moenan complex, concentrations of Ir decrease, and those of Pd and Os increase, toward the upper or apical parts of the complex.
Keywords: lode and placer deposits; platinum-group minerals; Gal’moenan massif; Koryak–Kamchatka Platinum Belt; Russia